Landscape Genetics: A Toolbox for Studying Vector-Borne Diseases - Hemming-Schroeder, Elizabeth; Lo, Eugenia; Salazar, Cynthia; Puente, Sandie; Yan, Guiyun (Frontiers in Ecology and Evolution, 2018)
Landscape genetics aims to quantify the effect of landscape on gene flow. Broadly, the approach involves measuring genetic variation, quantifying landscape heterogeneity, and statistically testing the link between both genetic variation and landscape heterogeneity. This approach has been widely used by conservation biologists, for example to identify barriers restricting movement in threatened populations. More recently, landscape genetics has been used to study the epidemiology of infectious diseases, such as chronic wasting disease, raccoon rabies, and malaria. This method can be useful to identifying potential hotspot areas of disease movement for targeted public health interventions and containment of disease and drug resistance. However, vector-borne disease epidemiology is particularly complex, as it is affected by the movement of both the vector and human or vertebrate host. This feature could potentially inhibit the ability to detect the effect of landscape on gene flow, since the ecology of vectors and hosts are likely different and potentially conflicting. Here, we provide a summary of the latest innovations in the field of landscape genetics with a focus on those that could help increase the power to detect landscape effects in vector-borne human disease studies. We also provide a recommended framework for studying vector-borne diseases using a landscape genetics approach. Landscape genetics has the potential to be a powerful tool for the field of vector-borne disease epidemiology, but has so far been underutilized. The provided synthesis of tools and considerations for conducting a landscape genetics study of a vector-borne disease aim to bridge the gap between the two disciplines.